Porcine Models of the Intestinal Microbiota: The Translational Key to Understanding How Gut Commensals Contribute to Gastrointestinal Disease - Rose, Elizabeth C.; Blikslager, Anthony T.; Ziegler, Amanda L. (Frontiers in Veterinary Science, 2022)
In the United States, gastrointestinal disorders account for in excess of $130 billion in healthcare expenditures and 22 million hospitalizations annually1,2. Many of these disorders, including necrotizing enterocolitis of infants, obesity, diarrhea, and inflammatory bowel disease, are associated with disturbances in the gastrointestinal microbial composition and metabolic activity. To further elucidate the pathogenesis of these disease syndromes as well as uncover novel therapies and preventative measures, gastrointestinal researchers should consider the pig as a powerful, translational model of the gastrointestinal microbiota. This is because pigs and humans share striking similarities in their intestinal microbiota as well as gastrointestinal anatomy and physiology. The introduction of gnotobiotic pigs, particularly human-microbial associated pigs, has already amplified our understanding of many gastrointestinal diseases that have detrimental effects on human health worldwide. Continued utilization of these models will undoubtedly inform translational advancements in future gastrointestinal research and potential therapeutics.